Dynamic fracture mechanics in the study of the earthquake rupturing process: theory and observation - Das, S (Elsevier, 2003)
Earthquake damage depends on the ground acceleration generated by ut, with this ground acceleration being directly proportional to the changes in rupture speed as a fault propagates. This is the primary motivation for seismologists to study earthquake fracture dynamics. The theoretical possibility of supersonic rupture speeds for faults with finite cohesion and friction was demonstrated in the 1970s, the theoretical developments spurring the search for such observations for earthquake ruptures, though unambiguous examples still remain elusive. Since rupture speed changes are related to the heterogeneity of the fault cohesion and friction, complex fault propagation models, namely the barrier and asperity models, and their associated radiated field have been studied. It was shown that a propagating rupture with finite cohesion can jump over strong barriers and continue propagating, leaving the barrier unbroken. Barriers of the size of a few kilometers to about 100 km have since been found in earthquakes. Even seemingly relatively simple physical situations, can lead to such complex rupturing processes that the usual idea of "rupture velocity" needs to be abandoned in those cases. The inverse problem of determining the details of the rupture process by analyzing recorded seismograms is one of the most vigorous areas of seismological research today.